2017
DOI: 10.1007/s00256-017-2754-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperextension injuries of the knee: do patterns of bone bruising predict soft tissue injury?

Abstract: Following knee hyperextension, bone bruising patterns may be associated with cruciate ligament injury. Other structures are injured less frequently and have weaker associations with bone bruise distribution. The double sulcus sign is a radiographic marker that confers a high probability of ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The knee joint relies on a variety of ligaments, muscles, tendons, bones, and cartilage to maintain flexibility, stability, and strength, is the largest and 1 of the most complex joints in the human body . The knee joint is susceptible to many types of injuries, including fractures, sprains, tears, and dislocations . Aging and joint diseases may lead to cartilage degeneration or injury, adversely affecting normal movements of the knee joint …”
Section: Introductionmentioning
confidence: 99%
“…The knee joint relies on a variety of ligaments, muscles, tendons, bones, and cartilage to maintain flexibility, stability, and strength, is the largest and 1 of the most complex joints in the human body . The knee joint is susceptible to many types of injuries, including fractures, sprains, tears, and dislocations . Aging and joint diseases may lead to cartilage degeneration or injury, adversely affecting normal movements of the knee joint …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most studies have focused on the lateral-medial direction of bone bruise locations, with little attention to the anterior-posterior direction. 1,2,10,19,23,28,31 Further, 2 recent systematic reviews concluded that further studies on bone bruise distribution patterns should be conducted to improve the accuracy of the bone bruise pattern. 25,38 Therefore, the purpose of this study was to investigate the common bone bruise patterns after an ACL injury.…”
mentioning
confidence: 99%
“…Hyperextension tibial plateau fractures are often accompanied by soft tissue (ligament and meniscus) injuries. Ali et al 18 . reported that 52% of 25 patients with hyperextension injuries were in the posterior joint capsule, 40% had ACL injuries, 20% had meniscus injuries, and 16% had medial and lateral collateral ligament and posterolateral horn injuries.…”
Section: Discussionmentioning
confidence: 99%